2023
DOI: 10.1186/s13046-022-02572-2
|View full text |Cite
|
Sign up to set email alerts
|

Parvimonas micra activates the Ras/ERK/c-Fos pathway by upregulating miR-218-5p to promote colorectal cancer progression

Abstract: Background Colorectal cancer (CRC) is the third most common cancer in the world, and a strong relationship exists between CRC and gut microbiota, which affects the occurrence, development, and metastasis of cancer. Bioinformatics-based analyses revealed that the abundance of Parvimonas micra (P. micra) in the feces of patients with cancer is significantly higher than that in healthy people. Therefore, an important relationship may exist between P. micra and CRC. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Of note, two species, Dialister pneumosintes and Parvimonas micra , were selected by Lasso and RF but not by StableMate (Figure 5B). In particular, Parvimonas micra is known to be associated with CRC as it promotes tumourigenesis (Chang et al, 2023; Zhao et al, 2022). However, StableMate identified these two species as predictive but not significantly stable.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, two species, Dialister pneumosintes and Parvimonas micra , were selected by Lasso and RF but not by StableMate (Figure 5B). In particular, Parvimonas micra is known to be associated with CRC as it promotes tumourigenesis (Chang et al, 2023; Zhao et al, 2022). However, StableMate identified these two species as predictive but not significantly stable.…”
Section: Resultsmentioning
confidence: 99%
“… P. micra is highly abundant in patients with colorectal cancer and promotes colorectal tumorigenesis by inducing colonocyte proliferation and altering the Th17 immune response ( 31 , 32 ). Our previous results showed that P. micra promoted colorectal cancer progression by upregulating miR-218-5p expression and ultimately activating the Ras/ERK/c-Fos signaling pathway ( 33 ). However, its correlation with lung cancer has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] proved that P. micra causes hypermethylations in the promoters of genes related to the cytoskeleton, such as SCIN and DIAPH3 , in tumor suppressor genes, such as TSPAN13 , HACE1 , SEMA3F and SASH1 , and in epithelial‐mesenchymal transition genes such FBXO32 , in colon cells. A recent study also demonstrated that these periodontal bacteria can also promote CRC development increasing the expression of a specific microRNA (miR‐218‐5p) in cells and exosomes, inhibiting the expression of PTPRR and enhancing the RAS/ERK/C‐FOS signaling pathway, which leads to colon cells overgrowth [ 105 ]. It is important to note that Zhao et al.…”
Section: Discussionmentioning
confidence: 99%